Analysis of Students' Learning Ability in Education Innovation Assisted in Learning Media Neo Snake and Ladder Game in the Society 5.0 Era - Zulela M. S; Edwita Edwita; Gusti Yarmi; Fauzi Fadliansyah; Anna Maria Oktaviani (Teknodika, 2022)
Educational innovation in the era of society 5.0 is important. However, social studies lessons are still low. Therefore, one way to improve the results of social studies lessons that are lacking is by means of learning media. One of them is the snake and ladder neo game media. The purpose of this study was to determine the effectiveness of Neo Snake and Ladder Game media in improving students' social studies skills in the era of society 5.0. The population in this study were fourth grade students of SD Negeri Cipocok Jaya, Serang, Banten, for the 2022/2023 academic year. The researcher used simple random sampling. Collecting data using social studies test questions and observations. The results showed that (1) the classical completeness test of social studies ability reached a minimum limit of 70, (2) social studies skill skills on Neo Snake and Ladder Game media had reached 75% classical completeness and (3) an increase in the average social studies skill using Neo media. Snakes and Ladders. The game is better than the average social studies ability of students without using Neo Snake and Ladder Games media. Based on the results above, it can be said that the Neo Snake and Ladder Games media is effective in improving students' social studies skills